The Role of Openness in Mediating The Involvement of Parents with Career Decision Making Self-Efficacy on JHS Participants in Semarang (Universitas Negeri Semarang, 2019)
This research aims to determine the relationship of parental involvement to career decision making self-efficacy with openness as a mediating variable. The sample involved 400 students selected using Cluster Random Sampling technique. Methods of data collection using an adapted psychological scale. Data analysis method used is descriptive analysis and mediation analysis with corrected method bias bootstrap technique with 95% confidential intervals. The results showed that parental involvement predicts career decision making self-efficacy and openness, then openness mediates the relationship of parent involvement and career decision making self-efficacy. This research provides counselors with an understanding of the relationship of parental involvement and the influence of personal aspects (self-efficacy and openness) in career selection.